RESPONSE OF EGGPLANT (Solanum melongena L.) TO COMBINATION OF INORGANIC-ORGANIC N AND EM4 - Maghfoer, Moch. Dawam; Soelistyono, Roedy; Herlina, Ninuk (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2013)
A research to reduce application of N inorganic fertilizer through combination of inorganic-organic N and EM4 on eggplant has done on paddy fieldin Poncokusumo, Malang Regency, East Java, from June to September 2013. The experiment used a randomized complete block design with two factors and three replications.The first factor was the combination of inorganic-organic N fertilizer, ie. 100% urea, 75% urea + 25% goat manure, 50% urea + 50% goat manure, and 25% urea + 75% goat manure . The second factor was dose of EM4, ie. 10, 20, and 30 liters EM4ha-1.The results showed a reduction in the proportion of urea up to 50% and replace it with goat manure resulted growth and fruit yield of eggplant better than the others. The application of 100% urea gave the lowest fruit yield. Application of EM4 on eggplant enhanced growth and increased fruit yield. EM4 application with doses of 30 litersha-1 resulted the highest fruit yield, accelerate the decomposition and mineralization of N. Keywords: eggplant, urea, goat manure, EM4, decomposition